Female-age-dependent changes in the lipid fingerprint of the mammalian oocytes - Bisogno, Simona; Depciuch, Joanna; Gulzar, Hafsa; Heber, Maria Florencia; Kobiałka, Michał; Gąsior, Łukasz; Bereta, Adrianna; Pieczara, Anna; Fic, Kinga; Musson, Richard; Garcia Gamero, Gabriel; Pardo Martinez, Maria; et al. (Human reproduction (Oxford, England), 2024)
STUDY QUESTION: Can oocyte functionality be assessed by observing changes in their intracytoplasmic lipid droplets (LDs) profiles? SUMMARY ANSWER: Lipid profile changes can reliably be detected in human oocytes; lipid changes are linked with maternal age and impaired developmental competence in a mouse model. WHAT IS KNOWN ALREADY: In all cellular components, lipid damage is the earliest manifestation of oxidative stress (OS), which leads to a cascade of negative consequences for organelles and DNA. Lipid damage is marked by the accumulation of LDs. We hypothesized that impaired oocyte functionality resulting from aging and associated OS could be assessed by changes in LDs profile, hereafter called lipid fingerprint (LF). STUDY DESIGN, SIZE, DURATION: To investigate if it is possible to detect differences in oocyte LF, we subjected human GV-stage oocytes to spectroscopic examinations. For this, a total of 48 oocytes derived from 26 young healthy women (under 33 years of age) with no history of infertility, enrolled in an oocyte donation program, were analyzed. Furthermore, 30 GV human oocytes from 12 women were analyzed by transmission electron microscopy (TEM). To evaluate the effect of oocytes' lipid profile changes on embryo development, a total of 52 C57BL/6 wild-type mice and 125 Gnpat+/- mice were also used. PARTICIPANTS/MATERIALS, SETTING, METHODS: Human oocytes were assessed by label-free cell imaging via coherent anti-Stokes Raman spectroscopy (CARS). Further confirmation of LF changes was conducted using spontaneous Raman followed by Fourier transform infrared (FTIR) spectroscopies and TEM. Additionally, to evaluate whether LF changes are associated with developmental competence, mouse oocytes and blastocysts were evaluated using TEM and the lipid dyes BODIPY and Nile Red. Mouse embryonic exosomes were evaluated using flow cytometry, FTIR and FT-Raman spectroscopies. MAIN RESULTS AND THE ROLE OF CHANCE: Here we demonstrated progressive changes in the LF of oocytes associated with the woman's age consisting of increased LDs size, area, and number. LF variations in oocytes were detectable also within individual donors. This finding makes LF assessment a promising tool to grade oocytes of the same patient, based on their quality. We next demonstrated age-associated changes in oocytes reflected by lipid peroxidation and composition changes; the accumulation of carotenoids; and alterations of structural properties of lipid bilayers. Finally, using a mouse model, we showed that LF changes in oocytes are negatively associated with the secretion of embryonic exosomes prior to implantation. Deficient exosome secretion disrupts communication between the embryo and the uterus and thus may explain recurrent implantation failures in advanced-age patients. LIMITATIONS, REASONS FOR CAUTION: Due to differences in lipid content between different species' oocytes, the developmental impact of lipid oxidation and consequent LF changes may differ across mammalian oocytes. WIDER IMPLICATIONS OF THE FINDINGS: Our findings open the possibility to develop an innovative tool for oocyte assessment and highlight likely functional connections between oocyte LDs and embryonic exosome secretion. By recognizing the role of oocyte LF in shaping the embryo's ability to implant, our original work points to future directions of research relevant to developmental biology and reproductive medicine. STUDY FUNDING/COMPETING INTEREST(S): This research was funded by National Science Centre of Poland, Grants: 2021/41/B/NZ3/03507 and 2019/35/B/NZ4/03547 (to G.E.P.); 2022/44/C/NZ4/00076 (to M.F.H.) and 2019/35/N/NZ3/03213 (to Ł.G.). M.F.H. is a National Agency for Academic Exchange (NAWA) fellow (GA ULM/2019/1/00097/U/00001). K.F. is a Diamond Grant fellow (Ministry of Education and Science GA 0175/DIA/2019/28). The open-access publication of this article was funded by the Priority Research Area BioS under the program "Excellence Initiative - Research University" at the Jagiellonian University in Krakow. The authors declare no competing interest. TRIAL REGISTRATION NUMBER: N/A.
Keywords: oxidační stres; Maternal Age; Aging; carotenoids; lipid droplets; oocyty; lipid analysis; Embryonic Development; Spectrum Analysis, Raman; Ramanova spektroskopie; Adult; dospělí; lipidová tělíska; exosomes; metabolismus lipidů; oocyte; coherent anti-Stokes Raman spectroscopy; Animals; lidé; ženské pohlaví; Microscopy, Electron, Transmission; Humans; věk matky; zvířata; Lipid Metabolism; myši inbrední C57BL; stárnutí; embryonální vývoj; myši; Mice, Inbred C57BL; Gnpat; Mice; Female; Oxidative Stress; Lipid Droplets; transmisní elektronová mikroskopie; Oocytes